Tombs of the South Asasif necropolis Thebes, Karakhamun (TT 223), and Karabasken (TT 391) in the twenty-fifth dynasty - Booth, Adam; Budka, Julia 1977-; Eigner, Dieter; Griffin, Kenneth; Ikram, Salima 1965-; Josephson, Jack A. 1930-; Molinero Polo, Miguel Ángel; Morkot, Robert; Naunton, Chris 1978-; Szpakowska, Kasia Maria (The American University in Cairo Press, 2014)
This volume is a joint publication of the members of the American-Egyptian mission South Asasif Conservation Project, working under the auspices of the State Ministry for Antiquities and Supreme Council of Antiquities, and directed by the editor. The Project is dedicated to the clearing, restoration, and reconstruction of the tombs of Karabasken (TT 391) and Karakhamun (TT 223) of the Twenty-fifth Dynasty, and the tomb of Irtieru (TT 390) of the Twenty-sixth Dynasty, on the West Bank of Luxor. These tombs, located in the South Asasif necropolis, were considered almost completely ruined by floods and constant re-usage. Therefore, when the project was initiated in 2006, the team was uncertain of the condition of the tombs and the amount of original material still remaining in the ruins and debris. The results of the first few years of work surpassed the most optimistic prognoses, of which there were not many. The tombs, as damaged as they are, have proved to be reconstructible, based on the thousands of fragments of the original decoration found during the clearing of the remains of the architectural features